Implementasi Metode SAW Pada Sistem Penunjang Keputusan Untuk Penerimaan Guru Di Pesantren Darul Mursyid - Akhiruddin Pulungan; Billy Hendrik (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
In order for the process of realizing good teaching and learning, it is also necessary to have a teacher who can indeed be respected as a teacher. Not only being able to convey learning material to students, but a teacher must also read the character of students, master the class, provide solutions, and replace the role as a parent if the child is at school. Therefore the quality of a school is very influential on its teaching staff. To support the good quality of the school, the most basic thing that can be done is to select teachers who will teach. In the teacher recruitment selection process, the Decision Support System (SPK) with the WAP method is one of the suitable methods to be applied to find out how big the ratio of the results of the selection is.